An uncondensed lignin depolymerized in the solid state and isolated from lignocellulosic biomass: a mechanistic study. Issue 18 (20th June 2018) - Li, Ning; Li, Yanding; Yoo, Chang Geun; Yang, Xiaohui; Lin, Xuliang; Ralph, John; Pan, Xuejun
Abstract : Lignin was depolymerized in the solid state and separated from lignocellulosic biomass in high-purity and in a less condensed form for valorization. Abstract : This study demonstrated that lignin could be efficiently depolymerized in the solid state with minimal condensation and separated from biomass with high purity by dissolving and hydrolyzing cellulose and hemicelluloses, using an acidic lithium bromide trihydrate (ALBTH) system under mild conditions (with 40 mM HCl at 110 °C). The ALBTH lignins isolated from biomass sources representing the three plant classes (hardwoods, softwoods, and grasses) contained abundant uncondensed moieties ( i.e., Hibbert's ketones and benzodioxanes). The benzodioxane structure was identified and confirmed for the first time in an acid-depolymerized lignin. Reactions using lignin model compounds (LMCs, guaiacylglycerol-β-guaiacyl ether and various aromatic monomers) confirmed the formation of the uncondensed moieties and revealed the synergy between LiBr and acid in inducing the crucial intermediate benzyl carbocations, which then led to cleavage of the β- O -4-aryl ether bonds to produce Hibbert's ketones, demethylation to produce benzodioxanes, and condensation reactions. Unlike in the LMC reactions, the condensation of the real lignin in biomass under ALBTH conditions was greatly diminished, possibly due to lignin remaining in the solid state, limiting its mobility and accessibility of the benzyl carbocation to the electron-rich aromatic sites for condensation. Preliminary results indicated that, because of its uncondensed nature, the ALBTH lignin was a good lignin feedstock for hydrogenolysis. This study provided a new approach to effectively isolate depolymerized lignin from lignocellulose in a less condensed form for boosting its downstream valorization.